Integrated assessment of eutrophication in Lake Rawa Pening, Central Java, Indonesia, using multivariate statistical methods - ARIF RAHMAN; HAERUDDIN HAERUDDIN; KUKUH PRAKOSO; DIANI ESTINING TYAS; OKTAVIANTO EKO JATI; ATIKA ARIFATI (Society for Indonesian Biodiversity, 2026)
Abstract. Rahman A, Haeruddin, Prakoso K, Tyas DE, Jati OE, Arifati A. 2026. Integrated assessment of eutrophication in Lake Rawa Pening, Central Java, Indonesia, using multivariate statistical methods. Biodiversitas 27 (5): d270519. https://doi.org/10.13057/biodiv/d270519. Lake Rawa Pening, located in Central Java, Indonesia, is a shallow tropical lake affected by anthropogenic eutrophication. This study aims to determine the lake's trophic status and explore association patterns among water quality variables. Water samples were collected at five stations over four periods (February 2024, July 2024, February 2025, and July 2025), representing the rainy and dry seasons. Trophic status was determined using Carlson’s Trophic State Index (TSI), while temporal variation and relationships among variables were analyzed using ANOVA, Pearson correlation, and Principal Component Analysis (PCA). Total Phosphorus (TP) used in TSI calculation was estimated from orthophosphate (PO4-P) based on an empirical conversion. Nitrate (0.28-0.80 mg/L) and orthophosphate (0.29-0.41 mg/L) concentrations were relatively high, while chlorophyll-a ranged from 8.39 to 38.05 mg/m3. All TSI values ​​exceeded 67, classifying the lake as hypereutrophic. Significant temporal differences were found for water depth, Secchi depth, water temperature, nitrate, and chlorophyll-a (p < 0.05). PCA identified dominant gradients associated with turbidity, nitrate, dissolved oxygen, and inverse relationships with Secchi depth and chlorophyll-a. These results indicate persistent eutrophication with multivariate interactions among water quality variables. Continuous water quality monitoring and integrated watershed management are crucial to prevent degradation and restore the balance of the Lake Rawa Pening ecosystem.